AN ANALYSIS OF SOCIOLINGUISTICS ASPECT OF SLANG IN â€SAVE THE LAST DANCE 2â€ MOVIE - Ni Putu Rika Suciasih; I Wayan Mawa; Ni Putu Wulantari (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2022)
This research is a descriptive qualitative research which attempt to find types and aspects sosiolinguistics in â€œSave The Last Dance 2â€ Movie. The subject of this research was movie entitles â€œSave The Last Dance 2â€ Movie. The datawere collected by observation technique watching the movie. Regarding to the first problem statement about type of slang used in Save The Last Dance 2 Movie, there are only four types of slang found in this movie. Thoseare Fresh and creative, flippant, imitative and clipping. The occurrence of Fresh and Creative dominates the slang type used in Save The Last Dance 2 Movie. It means that slang words have much a new vocabulary to say for informal situation and condition in different area.